Effects of photon irradiation in the presence and absence of hindlimb unloading on the behavioral performance and metabolic pathways in the plasma of Fischer rats - Raber, Jacob; Holden, Sarah; Kessler, Kat; Glaeser, Breanna; McQuesten, Chloe; Chaudhari, Mitali; Stenzel, Fiona; Lenarczyk, Marek; Leonard, Scott Willem; Morré, Jeffrey; Choi, Jaewoo; Kronenberg, Amy; et al. (Frontiers in Physiology, 2024)
Introduction: The space environment astronauts experience during space missions consists of multiple environmental challenges, including microgravity. In this study, we assessed the behavioral and cognitive performance of male Fisher rats two months after sham-irradiation or total body irradiation with photons in the absence or presence of simulated microgravity. We analyzed the plasma collected nine months after sham-irradiation or total body irradiation for distinct alterations in metabolic pathways and to determine whether changes to metabolic measures were associated with specific behavioral and cognitive measures. Methods: Male Fischer 344 rats were irradiated with photons (6 MeV; 3, 8, or 10 Gy) in the absence or presence of simulated weightlessness achieved using hindlimb unloading (HU). To identify potential plasma biomarkers of photon radiation exposure or HU condition for behavioral or cognitive performance, we used regression analyses. Results: The behavioral effects of HU on activity levels in the open field, measures of anxiety in the elevated plus maze, and anhedonia in the M & M consumption test were more pronounced than those of photon irradiation. Phenylalanine, tyrosine, and tryptophan metabolism and phenylalanine metabolism and biosynthesis showed very strong pathway changes following photon irradiation and following HU in animals irradiated with 3 Gy. There were 29 out of 101 plasma metabolites associated with 1 out of 13 behavioral measures. In the absence of HU, there were 22 metabolites related to behavioral and cognitive measures. In HU animals that were sham-irradiated or that were irradiated with 8 Gy, there was one metabolite that related to behavioral and cognitive measures. In HU animals irradiated with 3 Gy, there were 6 metabolites related to behavioral and cognitive measures. Discussion: These data suggest that it will be possible to develop stable plasma biomarkers of behavioral and cognitive performance following environmental challenges like HU and radiation exposure.